PTU-130 Regulatory T Cells In Acute Liver Failure Are Functionally Intact And May Contribute To Retention Of Neutrophils In Areas Of Hepatic Necrosis. (9th June 2014) - Chudasama, R; Chen, Y-Y; Jeffery, H; Thomas, C; Murphy, N; Whitehouse, T; Adams, DH; Oo, YH
Abstract : Introduction: Acute liver failure (ALF) is a sterile inflammation with a high mortality. The immunological response to acute liver injury is initiated by the infiltration of innate neutrophils and is followed by an adaptive T cells response. T cells in drug induced skin lesions have been shown to express neutrophil chemoattractant and there is also evidence that regulatory T cells (Tregs) in peripheral blood secrete IL-8. However, little is known on the ability of liver infiltrating T cell subsets to retain neutrophils in ALF or the function of Tregs. Our aim is to investigate the phenotypic features and cytokine profiles of circulating and liver infiltrating T cell subsets from ALF patients with a view of assessing their functional ability to retain neutrophils. Methods: Distribution and localisation of Liver infiltrating lymphocytes and neutrophils were assessed by immunohistochemistry. Peripheral blood and liver infiltrating lymphocytes were isolated from ALF patients. Intracellular-cytokines expression profiles of the lymphocytes subsets were assessed by flow cytometry. Functional status of T cells including Tregs was assessed by pSTAT5 signalling. Results: Immunohistochemistry revealed high numbers of neutrophils in ALF compared to chronic diseased livers (109 ± 12.2 vs. 7.1 ± 2.67; p = 0.01) and normal liver (109 ± 12.2 vs. 0.8 ± 0.33; p = 0.0002). Dual immunohistochemistry showed co-localisation of lymphocytes and neutrophils in areas of hepatic necrosis. Neutrophil chemoattractant IL-8 expression in peripheral blood was higher in lymphocyte subsets of ALF patients compared to normal donor, CD3 (2.3 ± 0.54% vs. 0.93 ± 0.4%; p = 0.23), CD4 (2.8 ± 2.2% vs. 1.1 ± 0.7%; p = 0.41), CD8 (2.2 ± 1% vs. 0.61 ± 0.09%; p = 0.43) and Treg (0.8 ± 0.4% vs. 0.2 ± 0.02%; p = 0.48). There was an up-regulation of IL-8 production in Tregs after 7 days of ex vivo expansion compared to day zero (1.63 ± 1% vs. 0.77 ± 0.42%; p = 0.44). IFN-γ expression in ALF peripheral blood compared with normal blood was (23.1 ± 6.2% vs. 11.1 ± 8.4%; p = 0.38) for CD3 (11.72 ± 2.3% vs. 7.8 ± 6.26; p = 0.5) for CD4 and (14.21 ± 3.04 vs. 9.95 ± 8.44; p = 0.58) for CD8 after day seven of ex vivo expression. Importantly, Tregs from both blood and explanted liver of ALF were functional indicated by STAT5 phosphorylation in response to IL-2. Conclusion: We demonstrated for the first time that lymphocyte subsets including Tregs in ALF produce IL-8, which may contribute to the retention of neutrophils in areas of hepatic necrosis in ALF. We also showed that Tregs and other T cells are functionally responsive to IL-2 in both blood and explanted liver tissue of ALF patients. Disclosure of Interest: None Declared.